Prevalence of Dissociative Experiences in Those Referred to Emergency Psychiatric Centers After Attempting Suicide - Ali Firoozabadi; Leila Razeghian Jahromi; Shokoofeh Yaghmaie (Baqiyatallah University of Medical Sciences, 2018)
Background: Dissociation is a symptom that can be related to traumatic childhood events. Dissociation in some cases is categorized in a distinct subgroup from other psychiatric disorders. Objective: The purpose of this study was to investigate the prevalence of dissociative experiences in patients who have attempted suicide and who have referred to an emergency psychiatric center. Methods: This was a cross-sectional epidemiological study in which dissociative experiences were evaluated in 98 patients who referred to Ibn Sina and Hafez hospitals after attempting suicide. In addition to determining the prevalence of these experiences, the relation between the symptoms and variables such as sex, age, marital status, education and suicide risk was determined. Results: There was a significant difference in the level of disappointment between married and single patients (P = 0.047). The mean disappointment score for the overall population was 11.92, which is in the normal range. There was no significant relationship between the dissociation score and level of disappointment (P = 0.933). The prevalence of dissociative experiences was found to decrease as the age of the patients increased (P = 0.006). There was no significant difference between the rate of suicide as reflected in the measurement of disappointment and dissociative symptoms. There was no significant relationship between DES score and other variables. Conclusion: One cause of psychological pressure in deciding to attempt suicide is family conflict. Many individuals who attempt suicide did not have a thought-out desire to take their lives, but attempted it impulsively in response to a periodic stressor.